Protein, energy, and amino acids digestibility of Spirulina (Arthrospira platensis) fed to snubnose pompano Trachinotus blochii and sobaity seabream Sparidentex hasta - Siddik, Aboobucker; Zehra, Seemab; Saleh, Reda; De Mello, Paulo H.; Laranja, Joseph L. Q.; Alghamdi, Majed A.; Al Shaikhi, Ali; Al Hafedh, Yousef; Glencross, B. D.; Mohamed, Asaad H. (Frontiers in Sustainable Food Systems, 2025)
Spirulina possesses multifunctional dietary properties, making it a promising ingredient in aquaculture feed formulations as a substitute for conventional feed components. In this study, we determined the apparent digestibility coefficients (ADCs) of Spirulina to understand the nutrient availability in feeds. The ADCs for crude protein, energy, and amino acids in Spirulina were evluated for snubnose pompano Trachinotus blochii (706.2 ± 121.2 g) and sobaity seabream Sparidentex hasta (200 ± 50.2 g). Both fish species were fed either a basal diet (D1), which serves as a reference diet with 55.8% crude protein and 9.8% crude lipid content, or a test diet (D2), containing dried Spirulina powder as the test ingredient, with 56.9% crude protein and 8.8% crude lipid. The feeding period lasted 15 days before collecting fecal samples. The Spirulina was found to be palatable for both snubnose pompano and sobaity seabream, and average feed intake showed no significant differences between the basal and test diets in either species. Diet apparent digestibility coefficients (DADC) for protein among the test diets fed to snubnose pompano and sobaity seabream were 83.9 and 83.2%, respectively. Ingredient apparent digestibility coefficient (IADC) for protein for the Spirulina ingredients was significantly higher in sobaity seabream (81.6%) than snubnose pompano (74.7%). The amino acid digestibility values were significantly higher in sobaity seabream, which reflects the higher protein ingredient digestibility for the sobaity seabream. Conversely, the amino acid digestibility values were lower in the snubnose pompano, corresponding to a lower protein digestibility of the ingredients used in the diet. The findings obtained from the present study provide valuable guidance for considering Spirulina as a dietary feed ingredient for specific fish species. Additionally, the findings highlight clear species-specific differences in Spirulina digestibility, revealing that sobaity seabream has better protein and amino acid digestibility than snubnose pompano.